The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Utilization of an Advanced Sensor network to determine fuel heating value and Real-Time net unit heat rate during transient operation - Keane Stewart; Connor Moran; Kensley Fowler; David McFarland; Kody Powell; Jacob Tuttle; Andrew Fry (Fuel, 2024)

Synergistic reduction of SO2 emissions while co-firing biomass with coal in pilot-scale (1.5 MWth) and full-scale (471 MWe) combustors - Rajarshi Roy; Spencer Bandi; Xiaolong Li; Brian Schooff; Regan Kuttler; Megan Aichele; Scott Montgomery; Jacob Tuttle; Stacey J. Smith; Jost O.L. Wendt; Brian D. Iverson; Andrew Fry (Fuel, 2024)

Patterns, causes and consequences of defensive microbiome dynamics across multiple scales - Andrew H. Smith; Piotr Łukasik; Michael P. O'Connor; Amanda Lee; Garrett Mayo; Milton T. Drott; Steven Doll; Robert Tuttle; Rachael A. Disciullo; Andrea Messina; Kerry M. Oliver; Jacob A. Russell (Molecular Ecology, 2015)
The microbiome can significantly impact host phenotypes and serve as an additional source of heritable genetic variation. While patterns across eukaryotes are consistent with a role for symbiotic microbes in host macroevolution, few studies have examined symbiont‐driven host evolution or the ecological implications of a dynamic microbiome across temporal, spatial or ecological scales. The pea aphid, Acyrthosiphon pisum , and its eight heritable bacterial endosymbionts have served as a model for studies on symbiosis and its potential contributions to host ecology and evolution. But we know little about the natural dynamics or ecological impacts of the heritable microbiome of this cosmopolitan insect pest. Here we report seasonal shifts in the frequencies of heritable defensive bacteria from natural pea aphid populations across two host races and geographic regions. Microbiome dynamics were consistent with symbiont responses to host‐level selection and findings from one population suggested symbiont‐driven adaptation to seasonally changing parasitoid pressures. Conversely, symbiont levels were negatively correlated with enemy‐driven mortality when measured across host races, suggesting important ecological impacts of host race microbiome divergence. Rapid drops in symbiont frequencies following seasonal peaks suggest microbiome instability in several populations, with potentially large costs of ‘superinfection’ under certain environmental conditions. In summary, the realization of several laboratory‐derived, a priori expectations suggests important natural impacts of defensive symbionts in host‐enemy eco‐evolutionary feedbacks. Yet negative findings and unanticipated correlations suggest complexities within this system may limit or obscure symbiont‐driven contemporary evolution, a finding of broad significance given the widespread nature of defensive microbes across plants and animals.